Rapid subacute myelopathy following kidney transplantation from HTLV-1 donors: role of immunosuppresors and failure of antiretrovirals - Roc, Lourdes; Mendoza, Carmen de; Fernández-Alonso, Miriam; Reina, Gabriel; Soriano, Vicente; Rodriguez, C.; ...et al.; Corral, Octavio Jorge; Gómez-Gallego, Felix (Therapeutic Advances in Infectious Disease, 2019)
Two kidney transplant recipients from a single donor became infected with HTLV-1 (human T-lymphotropic virus type 1) in Spain. One developed myelopathy 8 months following surgery despite early prescription of antiretroviral therapy. The allograft was removed from the second recipient at month 8 due to rejection and immunosuppressors discontinued. To date, 3 years later, this patient remains infected but asymptomatic. HTLV-1 infection was recognized retrospectively in the donor, a native Spaniard who had sex partners from endemic regions. Our findings call for a reappraisal of screening policies on donor–recipient organ transplantation. Based on the high risk of disease development and the large flux of persons from HTLV-1 endemic regions, pre-transplant HTLV-1 testing should be mandatory in Spain.
Keywords: antiretroviral drugs; HTLV-1; myelopathy; screening; transplantation; Emerging; Scopus